2012
DOI: 10.1371/journal.pone.0048505
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analysis of the Microbiota from the Crop of an Invasive Snail Reveals a Rich Reservoir of Novel Genes

Abstract: The shortage of petroleum reserves and the increase in CO2 emissions have raised global concerns and highlighted the importance of adopting sustainable energy sources. Second-generation ethanol made from lignocellulosic materials is considered to be one of the most promising fuels for vehicles. The giant snail Achatina fulica is an agricultural pest whose biotechnological potential has been largely untested. Here, the composition of the microbial population within the crop of this invasive land snail, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 67 publications
2
43
1
Order By: Relevance
“…At least one shipworm species (Lyrodus pedicellatus) has been shown to grow and reproduce normally using wood as its sole particulate food source (3). However, unlike their terrestrial herbivorous and xylophagous counterparts, whose digestive systems contain complex communities of microbes (4)(5)(6)(7)(8)(9), Bankia setacea and several other shipworm species accumulate and digest wood in the cecum ( Fig. 1 A and B), a region of the foregut that is devoid of any conspicuous microbial community (10).…”
mentioning
confidence: 99%
“…At least one shipworm species (Lyrodus pedicellatus) has been shown to grow and reproduce normally using wood as its sole particulate food source (3). However, unlike their terrestrial herbivorous and xylophagous counterparts, whose digestive systems contain complex communities of microbes (4)(5)(6)(7)(8)(9), Bankia setacea and several other shipworm species accumulate and digest wood in the cecum ( Fig. 1 A and B), a region of the foregut that is devoid of any conspicuous microbial community (10).…”
mentioning
confidence: 99%
“…In addition to their endo-genous enzymatic repertoire, recent studies revealed that land snails contain a complex and adaptable microbiota that potentially accounts for their great digestive efficiency [17,53,54]. In addition, a metagenomic analysis of A. fulica crop-resident microbiota identified a great number of sequences coding for biomass-degrading enzymes (36 %), including cellulases and hemicellulases [45]. Here, we have shown that Streptomyces sp.…”
Section: In Complexes C-[i] C-[ii] and C-[iii]mentioning
confidence: 75%
“…I1.2 is potentially an important representative of A. fulica microbiota that specifically contributes to nutrient acquisition during lignocellulose deconstruction through the secretion of complexed cellulases into the gastrointestinal lumen, which may provide complementary roles to noncomplexed endo-genous enzymes, such as distinct substrate preferences, kinetics, and/or higher hydrolysis rates. The importance of these complexed cellulase systems is highlighted by the fact that no cohesin or dockerin modules were detected in the contents of crop fluids [45], suggesting that the noncellulosomic multienzymatic complexes detected in this study represent a novel and alternative form of cellulolytic multienzyme complex organization, which is crucial for nutrient uptake in A. fulica.…”
Section: In Complexes C-[i] C-[ii] and C-[iii]mentioning
confidence: 86%
See 1 more Smart Citation
“…Bacteroidetes is a major bacterial group in many lignocellulose degrading environments, such as the crop of an invasive snail (36), and in the bagasse collection site, as shown by direct shotgun pyrosequencing (15). A recent study of genes encoding proteins related to cellulose utilization among 5123 sequenced bacterial genomes revealed that Bacteroidetes are highly represented as potent cellulose degraders in various environments (37).…”
Section: Discussionmentioning
confidence: 99%